Candiada Albicans Prototype Experimental Candidate Vaccines - Ibrahim Mohamed Saeed Shnawa (Vaccines and Vaccine Interference, 2023)
Whole cell live attenuated, whole cell killed, pan-fungal, conjugate, antibody, and DNA vaccine experimental strategies have been laboratory developed for prevention and therapy of mucosal and systemic C. albicans in an experimental prime and challenge mice models. These models have shown immune efficacy of 60-100 %.Recombinant peptide vaccine strategies have shown 100% efficacy in laboratory development and pass to phase I human clinical trials in mucosal and disseminated candidiasis models.